The Relationship between Gadget Addiction and Body Mass Index with Anemia in Teenage Girls - Idahafni Idahafni; Nurjanah Nurjanah; Basri Aramico; Asnawi Abdullah; Meutia Zahara (GLOBAL HEALTH SCIENCE GROUP, 2025)
Anemia is one of the nutritional problems that often occurs in teenagers, especially teenage girls. At this time teenage girls have also begun to depend on gadgets which have an impact on lack of physical activity, sleep pattern disorders and often miss time to eat because they forget. This study aims to determine the relationship between gadget addiction and body mass index (BMI) with the incidence of anemia in teenage girls at junior high schools in Teunom District Aceh Jaya Regency. This study is an analytical quantitative research using a cross-sectional approach. The sampling technique is a total sampling of 340 female adolescents, data collection techniques are carried out through the SAS google form and anthropometric examination. Data analysis uses chi-square and logistic regression. The results of this study showed that the variables that were most significantly related to the incidence of anemia in teenage girls included: teenage age (OR=1.5; 95%CI=1.14-2.07; p=0.004), maternal education (OR=3.09; 95%CI=1.86-5.14; p=0.000), gadget addiction (OR=3.09; 95%CI=1.15-8.32; p=0.025) and body mass index (OR=2.20; 95%CI=1.13-4.25; p=0.019).